2020
DOI: 10.18632/aging.103889
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin increases ICAM-1 expression and monocyte adhesion in human osteoarthritis synovial fibroblasts by reducing miR-320a expression

Abstract: Pathophysiological events that modulate the progression of structural changes in osteoarthritis (OA) include monocyte adhesion and infiltration, and synovial inflammation. In particular, the adhesion protein intercellular adhesion molecule type 1 (ICAM-1) promotes monocyte recruitment into the synovial tissue. Visfatin is an adipocyte hormone that promotes the release of inflammatory cytokines during OA progression. We report that visfatin enhances ICAM-1 expression in human OA synovial fibroblasts (OASFs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Double immunofluorescence staining of the synovium with macrophage marker CD68 and M1 macrophage marker CD86 revealed higher M1 expression in OA patients than in normal healthy individuals (Figure 1a,b). ICAM‐1‐regulated mononuclear cell adhesion to the synovial layer is an important process in OA disease (Law et al, 2020). Our IHC staining data revealed significantly elevated stages of ICAM‐1 and CD86 in OA synovial sample compared with samples from healthy individuals (Figure 1c–g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Double immunofluorescence staining of the synovium with macrophage marker CD68 and M1 macrophage marker CD86 revealed higher M1 expression in OA patients than in normal healthy individuals (Figure 1a,b). ICAM‐1‐regulated mononuclear cell adhesion to the synovial layer is an important process in OA disease (Law et al, 2020). Our IHC staining data revealed significantly elevated stages of ICAM‐1 and CD86 in OA synovial sample compared with samples from healthy individuals (Figure 1c–g).…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, activated macrophages (M2 macrophages) are stimulated by anti‐inflammatory mediators, for example, IL‐4 and IL‐13, and are capable of producing anti‐inflammatory regulators, including transforming growth factor beta (TGF‐β) and IL‐10 (Gordon & Taylor, 2005; Lumeng et al, 2007). Intercellular adhesion molecule‐1 (ICAM‐1) is among the various adhesion molecules that mediate macrophage adhesion to synovial tissue during OA disease (Ramos et al, 2014); higher levels of ICAM‐1 production are reported in human OA synovium than in healthy synovium (Koller et al, 1999; Law et al, 2020). Some researchers have recommended the suppression of ICAM‐1 synthesis in OA synovial tissue to inhibit the inflammatory process during OA (Law et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are critical post-transcriptional mediators of gene production and are found in several diseases, including OA [ 37 , 38 ]. It has been proposed that pharmacotherapy capable of controlling miRNA levels would inhibit OA inflammatory progression and thus be an appropriate therapeutic approach for this disease [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This upregulation occurs via p38/PI3K/Akt signaling pathway (Lin et al, 2019) (Figure 4). Interestingly, visfatin can also upregulate ICAM-1 via a p38-mediated suppression of miR-320a (Law et al, 2020).…”
Section: Role Of Visfatin In Adhesionmentioning
confidence: 99%